Development and characterization of polycrystalline transparent CsI plate for X-ray radiography applications. Issue 2 (15th January 2021) - Sen, Shashwati; Sarkar, P.S.; Patra, G.D.; Singh, S.G.; Ghosh, M.; Pitale, S.; Patil, A.N.; Pal, Manoj K.
Abstract: In this paper we report a novel way of processing CsI powder into poly-crystalline transparent plate by vacuum hot pressing technique. The fabricated CsI plate is investigated for its microstructure and phase purity. Further we have measured the luminescence and scintillation characteristics of this plate. These measurements establish that the polycrystalline plate can have application in radiation detection. Further the efficacy of the transparent CsI plate is shown for industrial X-ray radiography applications. Our results show that this kind of CsI plate can be economically fabricated and can replace the use of CsI single crystals and thin films in specific applications like radiation detection and industrial radiography.